2008
DOI: 10.1080/14017430802061656
|View full text |Cite
|
Sign up to set email alerts
|

Improved long-term survival following infrarenal abdominal aortic aneurysm repair

Abstract: Women with ruptured AAA have a higher early mortality than men, which needs to be investigated further. Long-term survival has improved during the study period. Age, diabetes, chronic obstructive pulmonary disease, renal failure and cerebrovascular insufficiency influenced the long-term survival negatively. EVAR is used to an increasing extent and the results are improving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Two studies reported the influence of carotid disease but these were not included in this group as carotid disease is not primarily associated with all strokes and carotid disease was poorly defined. 16,37 Nine studies 17,19,24,27,28,31,38,44,59 reported the influence of cerebrovascular disease on late survival resulting in a pooled HR 1.57 (95% CI 1.40e1.77) I 2 ¼ 0%. The presence of carotid disease had a HR 1.27 (95% CI 0.93e1.73) I 2 ¼ 0%.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Two studies reported the influence of carotid disease but these were not included in this group as carotid disease is not primarily associated with all strokes and carotid disease was poorly defined. 16,37 Nine studies 17,19,24,27,28,31,38,44,59 reported the influence of cerebrovascular disease on late survival resulting in a pooled HR 1.57 (95% CI 1.40e1.77) I 2 ¼ 0%. The presence of carotid disease had a HR 1.27 (95% CI 0.93e1.73) I 2 ¼ 0%.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Berge et al 31 Faizer et al 32 Hultgren et al 33 Bonamigo et al 34 Haug et al 35 Leon et al 36 Lifeline 20…”
Section: Mortality Ratementioning
confidence: 99%
“…Berge et al 31 Ting et al 52 Azizzadeh et al 53 Biebl et al 54 Leon et al 36 Lifeline 20 Zarins et al 55 Sampaio et al 56 Criado et al 57 Elkouri et al 58 Nordness et al 59 Parlani et al 60 Shames et al 61 Slovut et al 62 Wyers et al 63 Sanchez et al 64 Wolf et al 65 1 1·54 1·22 Howell et al 66 Mathison et al 67 Romero et al 68 Cao et al 69 Pooled odds ratio 35 23 82 80·8 8 2 ·2 68 65 2 (9) 9 (11) Leon et al 36 2746 7974 73·2(8·0)# 71·4(8·0)# --225 (8·2)** 415 (5·2)** Lifeline 20 69 37 42 177 69·9 ‡ 69·9 ‡ --5 (12)** 3 (1·7)** Urbonavicius et al 38 17 52 ----3 (18) 5 (10) Rigberg et al 9 18 71 ----0 (0)** 0 (0)** Sasaki et al 39 11 89 71 ‡ 71 ‡ 57·9(10·2) ‡ 57·9(10·2) ‡ 0 (0)** 1 (1)** Stenbaek et al 40 109 488 71(6·4) 70 (7) --12 (11·0) § 42 (8·6) § Biancari et al 41 239 42 68 90 70·3 ‡ 70·3 ‡ 58 ‡ 58 ‡ 1 (1) 4 (4) Rayan et al 43 100 321 74·4(7·1) ‡ 74·4(7·1) ‡ --2 ( 2 ·0)** 5 (1·6)** Alonso-Pérez et al 44 13 170 77 ‡ 77 (2)…”
Section: Favours Women Favours Menmentioning
confidence: 99%
See 2 more Smart Citations